Desenvolvimento de modelo transiente fuzzy de transporte de massa - estudo do risco ambiental em rios naturais a partir dos parâmetros de análise de DBO e OD - Lucena, Karyna Oliveira Chaves de (2018)
Due to the increasing degradation of the water bodies quality and the water scarcity scenario, it is important to know the behavior of these resources under different scenarios of effluent releases. For this purpose, mathematical models have been developed to represent processes of water quality, of high complexity, that present diverse parameters, in temporal and spatial variability, as it happens in fluvial systems. In this context, this work promoted the development of a methodology capable of evaluating the environmental risk of a natural river subject to effluent discharge, according to the Fuzzy theory. The methodology of the model was based on the principles of mass transport in conjunction with the Law of Fick, to calculate the concentration fields of the Biochemical Oxygen Demand, Dissolved Oxygen and Dissolved Oxygen Deficit in natural river; being considered the contributions from the following diffuse sources: sedimentation, nitrification, photosynthesis and respiration. The partial equations obtained in the model were submitted to the mathematical fundamentals of the Fuzzy theory, to insert the uncertainties linked to the water system, by means of pertinence functions, in order to allow the analysis of the reliability and risk of environmental degradation. For that, a computational program was developed, in FORTRAN language, capable of allowing the realization of the simulations in different scenarios of point source pollution and diffuse diffusion. The results of the model, in particular, in the concentration field of Biochemical Oxygen Demand and Dissolved Oxygen, corresponded to the profiles found in the literature, indicating that the use of the Fuzzy theory, added to the models of transport of pollutants, is presented as a an important alternative capable of providing subsidies for the management of water resources. The incorporation of the analysis of the risk of contamination of the river to the developed model reinforces the importance of this computational tool because it allows to anticipate possible impacts, highlighting the time and the region of the occurrence of this event.